Commitment Controls - Khemani, Pokar (Technical Notes and Manuals; Technical Notes and Manuals ;, 2009)
This technical note elaborates the objectives of commitment controls. The focus on commitment controls is justified on the grounds of their important role in developing an overall expenditure control framework, as well as controlling the accumulation of payment arrears. The note describes the preconditions for successful implementation of commitment controls. It elaborates the main institutional forms and operational arrangements of commitment controls. Implications for the IMF's operational work and technical assistance are also discussed.